Account of the Plate-Marks used in Scotland since the year 1457, and Chronological List of those of Edinburgh from 1681; to which is added a Note of those used in Glasgow - Sanderson, James H (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article discusses the use of plate-marks in the study of precious metals in Scotland. The author explains the purpose of each plate-mark from the Edinburgh Assay Office and the parliamentary act associated with it.